Modeling the distribution of mountain permafrost in the central Andes, San Juan, Argentina - Schreiber, Erika Amber Patin (University of Delaware, 2015)
O'Neal, Michael A. In the Dry Andes of San Juan, Argentina, interpreting the presence and climatic significance of many modern cryogenic landforms is an important step in understanding the potential impacts of mining operations. We investigate the distribution of permafrost at two Andes study sites (31° 05' S and 31° 29' S), where permafrost is protected by law as a periglacial feature and is of particular concern as a source of water for local peoples. Discontinuous permafrost zones are predicted based on thresholds of mean annual ground temperature (MAGT) and bottom temperature of winter snow (BTS). We employ a multiple linear regression model to determine these temperatures across the landscape using a dataset of topographic, geographic, and solar radiation information from 69 ground temperature sensor locations. Our results are tested against field knowledge and reveal that the classic BTS method is less accurate than MAGT in predicting the permafrost condition; however, verifying ice extent proves difficult in this landscape. Ultimately, the permafrost maps provided herein are a first step in better understanding water resources in this region. University of Delaware, Department of Geography M.S.